Fixed Points for w-Contractive Multimaps - Abdul Latif; Marwan A. Kutbi (International Journal of Mathematics and Mathematical Sciences)
Using the generalized Caristi's fixed point theorems we prove the existence of fixed points for self and nonself multivalued weakly w-contractive maps. Consequently, Our results either improve or generalize the corresponding fixed point results due to Latif (2007), Bae (2003), Suzuki, and Takahashi (1996) and others.